Synchronous appearance of gastrointestinal stromal tumor and neuroendocrine tumor in stomach: Review of the literature and management strategies - Deniz Güney DUMAN; Funda EREN; Ender Güneş YEĞİN; Aygün İKİNCİ; Cumhur YEĞEN (Turkish Journal of Gastroenterology, 2019)
-